Proximate Composition of Heat Treated Poultry Litter (Layers) - Owen, O. J.; Ngodigha, E.M.; Amakiri, A.O. (International Journal of Poultry Science, 2008)
Proximate composition was conducted to investigate the nutrient quality of heat treated poultry litter. The litter was subjected to heat treatment by deep stacking at temperature range of 40.10-55oC (104.20-31oF) for 21 days. This was done to ensure pathogenic microbial safety when used as animal feed supplement. Results obtained on the chemical composition showed that poultry litter (layers) contained 621.41 ME kcal/kg, 87% DM, 20% CP, 10.40% CF, 2.20 EE and 18.50% Ash. The results on mineral composition indicates that poultry litter has 4.5% Phosphorus (P), 2.00% Calcium (Ca), 0.10% Sodium (Na), 2.05% Potassium (K) and 0.48% Magnesium (Mg). This study on proximate composition of poultry litter shows that it could be incorporated into animal feeds.